The role of Kurdish women in the political events of the Middle Ages - Anwar, Prof.Dr.Keywan Azad (Sulaimani Journal for Humanities, 2026)
As a female and an influential force in the family and society, she is considered to be one of the components of society, which has played its role in most areas of life alongside men and men. Without women, there would be no marriage, no family, no meaning in life and no continuity in life. This study was prepared to highlight the role of Kurdish women in the political events of the Middle Ages. For this purpose, we divided the research into two sections. In the first discussion, we focused on the identity and characteristics of Kurdish women and their duties and rights in medieval society. The second discussion was devoted to the role of Kurdish women in the political events of that period. Finally, this work concludes with a conclusion and the sources used for this study. We hope that it will live up to the credibility of this international scientific conference.